Kajian Pelaksanaan Skema Cap and Tax dalam Kebijakan Mitigasi Perubahan Iklim Indonesia - Zefanya, Anastasia; Kennedy, Posma Sariguna Johnson (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
This research aims to analyze the implementation of the Cap and Tax scheme in climate change mitigation policies in Indonesia from 2015 to 2021. The Cap and Tax scheme is a climate change mitigation policy that sets an upper limit (cap) on the amount of greenhouse gas emissions that are subject to tax ( tax) on companies that exceed these limits. This research highlights how the Cap and Tax scheme is implemented in Indonesia, including the process of determining the cap, market mechanisms for emissions permits, and collecting funds from the carbon tax. The research method used is document analysis and interviews with respondents regarding policies. The research results show that the implementation of the Cap and Tax scheme in Indonesia has experienced several obstacles, including determining the appropriate cap, inadequate company participation, and an ineffective emission permit market mechanism. However, this scheme is still considered an important climate change mitigation policy and must continue to be improved to achieve better greenhouse gas emission reduction goals in the future.